Seedling Survival at Timberline Is Critical to Conifer Mountain Forest Elevation and Extent - Brodersen, Craig R.; Germino, Matthew J.; Johnson, Daniel M.; Reinhardt, Keith; Smith, William K.; Resler, Lynn M.; Bader, Maaike Y.; Sala, Anna; Kueppers, Lara M.; Broll, Gabriele; Cairns, David M.; Holtmeier, Friedrich-Karl; et al. (Frontiers in Forests and Global Change, 2019)
Conifer mountain forests influence a large portion of the World’s human population by providing a host of critical economic, sociological, and ecosystem services. Although the causes of the elevational, transitional boundaries of these forests (i.e. upper and lower timberlines) have been questioned for over a century, these investigations have focused predominately on the growth limitations of saplings or mature trees at the upper alpine boundary. Yet, the elevational movement of timberlines is dependent initially on new seedling establishment in favorable microsites that appear to be generated by ecological facilitation. Recent evidence suggests that this facilitation is critical during the initial 1-2 years of growth when survival may be less than a few percent, only cotyledons are present, and survival occurs only in favorable microsites created by inanimate objects (e.g. boulders, dead stems), microtopography, or already established vegetation. Dramatic changes in tree form (e.g. krummholz mats) across the timberline ecotone also plays an important role in generating microsite facilitation. These favorable, facilitated microsites have been characterized broadly as experiencing low sky exposure during summer (day and night) and leeward wind exposure during winter that generates protective snow cover, all of which are needed for new seedling survival. Thus, determining the specific microclimate and edaphic characteristics of favorable microsites, and their frequency at timberline, will provide a more mechanistic understanding and greater predictability of the future elevation and extent of conifer mountain forests. In addition, although the ecophysiological advantages of a needle-like leaf morphology is well established for adult conifer trees, the advantage of this phylogenetically unique trait in emergent seedlings has not been thoroughly evaluated. Understanding seedling ecophysiology and the functional morphology that contributes to survival, plus the nature and frequency of favorable microsites at timberline, will enable more reliable estimates of future elevational shifts in conifer mountain forests. This approach could also lead to the development of a valuable and sensitive tool for forest managers interested in evaluating future changes in these forests under increased large-scale infestation and drought mortality, as well as for current scenarios of predicted climate change.